MENJAGA MEMORI, MERAWAT BUDAYA, MENUJU SDGs: PERAN TRANSFORMASIONAL PERPUSTAKAAN DI ERA MODERN: Peran Transformasional Perpustakaan di Era Modern - Kusnandar; Samon CMS; Evi Nursanti Rukmana (PT. RANESS MEDIA RANCAGE, 2025)
Libraries as institutions of cultural memory and preservation have a crucial role in preserving the nation's cultural heritage and supporting the achievement of the Sustainable Development Goals (SDGs). This article examines the transformational role of libraries in the modern era, focusing on three main aspects: (1) the library's role as a repository and manager of collective memory, (2) its contribution to cultural preservation, and (3) its support for the SDGs, particularly in education, social inclusion, and access to information. Through a literature review and case studies, this article concludes that libraries are not only centers of knowledge, but also agents of change that promote sustainable development. Through preservation and digitization, libraries ensure that collective memory is preserved and accessible to future generations. In addition, libraries also play a role as cultural preservers, by preserving and promoting local cultures to raise public awareness about the importance of maintaining cultural diversity. Furthermore, libraries actively contribute to supporting the achievement of the SDGs, particularly in quality education, reducing inequality, and building inclusive institutions. By providing equitable access to information, supporting digital literacy, and serving as safe spaces for social dialog, libraries help communities address global challenges such as poverty, inequality, and climate change. Government and community support is essential to strengthen the strategic role of libraries in preserving collective memory, nurturing culture and creating a sustainable future. By continuing to innovate and adapt, libraries are expected to remain relevant and become an important pillar in global development.